Identifikasi Wilayah Rawan Banjir Kota Bandar Lampung Dengan Aplikasi Sistem Informasi Geografis (SIG) - Didik Kuswadi; Iskandar Zulkarnain; Suprapto Suprapto (Jurnal Ilmiah Teknik Pertanian - TekTan, 2014)
Development and deforesting were quite in many parts of Indonesia. Change of function become impervious land caused an imbalance of hydrology and watershed conditions. The objective  of this research were (1) to determined the class of a flood- prone of Bandar Lampung City, (2) to made a map of flood- prone of  Bandar Lampung City. Based on the research, it can be some results: (1) The class interval of flood- prone is 100; (2) Flood- prone  levels of Bandar Lampung District is divided into five classes, namely: very low, low, medium, high, very high; (3) The domination of flood- prone area of Bandar Lampung City was medium, the areas of this is 104.74 km2 (57.28%); (4) The highest potential flood- prone was Western Telukbetung sub districkt, that they had the condition were the slope is flat, soil type was inceptisols, height of land was 0.0 to 12.5m from sea water level, and rainfall was high. Keywords: identification, flood-prone, geographical information system